Photoreduction of carbon dioxide and photodegradation of organic pollutants using alkali cobalt oxides MCoO2 (M = Li or Na) as catalysts. (1st July 2022) - Chen, Hung-Lin; Liu, Fu-Yu; Xiao, Xinyu; Lin, Yu-Yun; Hu, Jing; Liu, Guan-Yo; Gao, Bo; Zou, Dechun; Chen, Chiing-Chang
Abstract: The recycling of lithium batteries should be prioritized, and the use of discarded alkali metal battery electrode materials as photocatalysts merits research attention. This study synthesized alkali metal cobalt oxide (MCoO2, M = Li or Na) as a photocatalyst for the photoreduction of CO2 and degradation of toxic organic substances. The optimized NaCoO2 and LiCoO2 photocatalysts increased the photocatalytic CO2 –CH4 conversion rate to 21.0 and 13.4 μmol g −1  h −1 under ultraviolet light irradiation and to 16.2 and 5.3 μmol g −1  h −1 under visible light irradiation, which is 17 times higher than that achieved by TiO2 P25. The rate constants of the optimized reactions of crystal violet (CV) with LiCoO2 and NaCoO2 were 2.29 × 10 −2 and 4.35 × 10 −2  h −1, respectively. The quenching effect of the scavengers and electron paramagnetic resonance in CV degradation indicated that active O2 −, 1 O2, and h + play the main role, whereas OH plays a minor role for LiCoO2 . The hyperfine splitting of the DMPO− OH and DMPO− CH3 adducts was aN  = 1.508 mT, aHβ  = 1.478 mT and aN  = 1.558 mT, aHβ  = 2.267 mT, respectively, whereas the hyperfine splitting of DMPO + was aN  = 1.475 mT. The quenching effect also indicated that active O2 − and h + play the main role and that OH and 1 O2 play a minor role for NaCoO2 . The hyperfine splitting of the DMPO− OH and DMPO + adducts was aN  = 1.517 mT, aHβ  = 1.489 mT and aN  = 1.496 mT, respectively. Discarded alkali metal battery electrode materials can be reused as photocatalysts to address environmental pollution. Graphical abstract: Image 1 Highlights: The use of discarded alkali battery electrode as photocatalysts merits research attention. CO2 photocatalytic rate of NaCoO2 are 21.0 and 16.2 μmol g −1  h −1 under UV and Vis light irradiation. CO2 photocatalytic rate of LiCoO2 are 16.2 and 5.3 μmol g −1  h −1 under UV and Vis light irradiation. The k of the optimized reactions of CV with LiCoO2 and NaCoO2 were 2.29 × 10 −2 and 4.35 × 10 −2  h −1 .